ETHICAL DEVELOPMENT AND IMPLEMENTATION OF ARTIFICIAL INTELLIGENCE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The paper discovers an essence and importance of introduction of ethical dimension in all phases of artificial intelligence (AI): development of concept and source code, implementation in real-life applications and support and improvement of existing solutions. Modern society largely depends on cybertechnologies most of which are using elements of AI and ethical aspects of it is of paramount importance.